Yield response and validation of CROPWAT for baby corn under drip irrigation - KUMAR, MUKESH; KUMAR, ROHITASHW (Journal of Soil and Water Conservation, 2023)
A study was conducted in 2020-21 to evaluate the optimal irrigation levels for maximum baby corn production with CROPWAT irrigation model using the data for baby corn cultivation round the year (three season). The irrigation was applied alternative days at three system operating pressures such as 0.5 kg cm-2; 1.0 kg cm-2 and 1.5 kg cm-2 using drip irrigation replicated three times. The irrigation water requirement along with scheduling of baby corn crop was determine using FAO-CROPWAT 8.0 software. The crop water requirement during three seasons i.e. 1, 2 and 3 were found 22.4, 60.7 and 61.7 mm, respectively. The results of data analysis showed that yield of baby corn was not significantly (P<0.05) affected by system operating pressures. However, lower crop yield of baby corn was recorded with system operating pressure of 1.5 kg cm-2. Highest yield of baby corn and fodder was recorded at system operating pressure of 1.0 kg cm-2 followed by a system operating pressure of 0.5 kg cm-2. The results showed that with increase in system operating pressure, there was a decrease in total yield baby corn due to more spread of water reduced uptake of water. The CROPWAT irrigation model was validated using field data for baby corn cultivation. Accordingly, the efficiency of the model was found to be 94%, indicating that the model is a useful decision support system to help baby corn growers.